Role of Copper Species in Copper Phyllosilicate Catalysts for the Catalytic TransferHydrogenation of Furfural to __Valerolactone - Tanyarat Shoosri; Sutarat Thongratkaew; Bunyarat Rungtaweevoranit; Wasawat Kraithong; Kajornsak Faungnawakij; Thapong Teerawatananond; Tawan Sooknoi; Sanchai Kuboon; Joongjai Panpranot; Patcharaporn Weerachawanasak (My University, 2024)
Copper phyllosilicate (CuPS) catalysts were synthesized and evaluated for the catalytic transfer hydrogenation of furfural to γ‐valerolactone (GVL). Various copper loadings (10‐30 wt.%) were studied to elucidate the impact of copper species on catalytic performance. Notably, a high dispersion of copper (%DCu ≈ 70%) and a substantial BET surface area (620 m²/g) were achieved, even at 30 wt.% copper loading. TR‐XANEs and XPS analyses identified two geometric structures of Cu²⁺ on the CuPS catalysts; square planar and octahedral alongside Cu⁺/Cu⁰ species formed upon reduction. The reduced 30%CuPS‐R catalyst, enriched in metallic Cu⁰, achieved complete conversion of furfural but exhibited low GVL selectivity. Conversely, the as‐synthesized 30%CuPS, predominantly composed of Cu²⁺, showed a lower furfural conversion but higher selectivity. The physical mixing of 30%CuPS‐R and 30%CuPS in a 50:50 ratio yielded the best catalytic performance, resulting in 100% furfural conversion and 86% GVL selectivity. The findings suggest that metallic Cu⁰ is essential for initiating the conversion of furfural, while Cu²⁺ plays a critical role in GVL formation. An optimal Lewis/Brønsted acidity ratio is determined to be 5.7 for the mixed catalysts. The proposed reaction mechanism underscores the complex interplay between different copper species and acid sites in CuPS catalysts.
Keywords: Catalysis and Hydrodesulfurization Studies